Diversity and composition of the microbiome associated with eggs of the Southern green stinkbug, Nezara viridula (Hemiptera: Pentatomidae). Issue 6 (7th December 2022) - Geerinck, Margot W. J.; Van Hee, Sara; Gloder, Gabriele; Crauwels, Sam; Colazza, Stefano; Jacquemyn, Hans; Cusumano, Antonino; Lievens, Bart
Abstract: Although microbial communities of insects from larval to adult stage have been increasingly investigated in recent years, little is still known about the diversity and composition of egg‐associated microbiomes. In this study, we used high‐throughput amplicon sequencing and quantitative PCR to get a better understanding of the microbiome of insect eggs and how they are established using the Southern green stinkbug Nezara viridula (L.) (Hemiptera: Pentatomidae) as a study object. First, to determine the bacterial community composition, egg masses from two natural populations in Belgium and Italy were examined. Subsequently, microbial community establishment was assessed by studying stinkbug eggs of different ages obtained from laboratory strains (unlaid eggs collected from the ovaries, eggs less than 24 h old, and eggs collected 4 days after oviposition). Both the external and internal egg‐associated microbiomes were analyzed by investigating egg washes and surface‐sterilized washed eggs, respectively. Eggs from the ovaries were completely devoid of bacteria, indicating that egg‐associated bacteria were deposited on the eggs during or after oviposition. The bacterial diversity of deposited eggs was very low, with on average 6.1 zero‐radius operational taxonomic units (zOTUs) in the external microbiome and 1.2 zOTUs in internal samples of egg masses collected from the field. Bacterial community composition and density did not change significantly over time, suggesting limited bacterial growth. A Pantoea ‐like symbiont previously found in the midgut of N. viridula was found in every sample and generally occurred at high relative and absolute densities, especially in the internal egg samples. Additionally, some eggs harbored a Sodalis symbiont, which has previously been found in the abdomen of several insects, but so far not in N. viridula populations. We conclude that the egg‐associated bacterial microbiome of N. viridula is species‐poor and dominated by a few symbionts, particularly the species‐specific obligate Pantoea ‐like symbiont. Abstract : In this study, we assessed the composition and establishment of the microbiome of insect eggs using the Southern green stinkbug Nezara viridula (Hemiptera: Pentatomidae) as a study object. Our results show that the egg‐associated bacterial microbiome is species‐poor and dominated by a few symbionts, particularly the species‐specific obligate Pantoea ‐like symbiont.